THE IMPACT OF DIGITALIZATION ON STATUTORY AUDITING IN SERBIA - Gruslav, Jelena; Knežević, Goranka; Perić, Miroslav (The European Journal of Applied Economics, 2026)
Digitalization is profoundly transforming audit operations in Serbia, significantly enhancing audit processes’ efficiency, accuracy, and speed. This paper investigates how the adoption of digital tools and technologies is reshaping traditional audit methodologies. Key advancements include the integration of data analytics, automated systems, and blockchain technology, which collectively revolutionize the way auditors conduct reviews and assessments. The digital shift is not merely about adopting new tools; it fundamentally alters the skill sets required for today’s auditors. Professionals must now navigate complex digital environments, develop competencies in data interpretation, and harness analytical tools to derive meaningful insights from vast amounts of information. Emerging challenges, such as cybersecurity threats, also require auditors to stay vigilant and responsive to safeguard sensitive data. While digitalization offers substantial benefits—including increased data precision, enhanced reporting capabilities, and streamlined workflows—it also necessitates substantial adaptation. Firms must invest in innovative technologies, upgrade their infrastructure, and prioritize ongoing skill development to effectively leverage these advancements. This strategic focus will allow audit firms to remain competitive in a rapidly evolving landscape while addressing the multifaceted challenges posed by the digital age. Ultimately, embracing digitalization is crucial for enhancing the value and effectiveness of audit services in Serbia.